ASSESSING KNOWLEDGE ON POST-PARTUM DEPRESSION AMONG MOTHERS AT THE TAMALE TEACHING HOSPITAL - Abdulai, A.; Muktar, A– M. (UDS International Journal of Development, 2023)
Postpartum depression, also referred to as postnatal depression, is a non-psychotic depressive disorder of variable severity and it can initiate as early as two weeks after delivery and can persist indefinitely if untreated and has been found to cause distress and impairs a mother’s ability to carry out her normal duties, care for herself and care for her baby. The study sought to assess the knowledge of postpartum depression among pregnant women at the Tamale Teaching Hospital. The study employed a descriptive cross-sectional study design. The study population included mothers who were attending postnatal care at the Tamale Teaching Hospital. 132 participants were consecutively sampled for the study. Completed questionnaire was entered into Statistical Package for the Social Science (SPSS version 22.00). Descriptive statistics including mean, percentages, and frequencies were calculated and presented in graphs and tables for quantitative variables. Cross tabulation using chi square was used to determine the association between dependent and independent variables. The mean age of respondents was 22 years. Majority of the respondents (95.3%) were between the ages of 25-34 years. Majority of respondents have ever heard of postpartum depression (63.6%) with health facility being the most cited source of information. The preferred sex of baby mothers wanted to have during and after pregnancy was significantly associated with postpartum depression with p values = <0.001. Also, unplanned pregnancy also showed a borderline association with postpartum depression with a p value = 0.051. Family support in taking care of the baby’s everyday needs was significantly associated with postpartum depression with p value =0.033. Mothers who did not get support from their families in taking care of their babies were more likely to experience depression than those who get support from their families. Mothers who were 35years and above had increased odds of getting postpartum depression as compared to those who were 25 to 34 years (OR=2.63; p<0.01). On the whole the study showed that partner support and maternal factors such as age and unplanned pregnancies were identified as the main determinants of postpartum depression among postpartum mothers seeking care at the Tamale Teaching Hospital.Key Words: Postpartum, Depression, Risk factors, Knowledge